Pengaruh Ekspor, Impor, Defisit Fiskal, Dan Utang Luar Negeri Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2017 – 2020 - Fahrina Shintya; Djoko Wahyudi (Universitas Sains dan Teknologi Komputer, 2022)
Economic growth is a process of economic change that occurs in a country on an ongoing basis to lead to changes for the better over a certain period of time. The development of the Indonesian economy cannot be separated from the influence of various factors, including factors from abroad. Economic growth is influenced by several factors including exports, imports, fiscal deficits, and foreign debt. This study aims to determine the effect of exports, imports, fiscal deficits and foreign debt on economic growth in Indonesia for the 2017-2020 period. The sample selection in this study used the cluster sampling method because the objects and data sources to be studied were very broad, consisting of 34 provinces in Indonesia, the total data used was 680 samples. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that exports have a negative and significant effect on economic growth. Imports have a positive and insignificant effect on economic growth. The fiscal deficit has a positive and insignificant effect on economic growth. Foreign debt has a positive and significant effect on economic growth. Further researchers can also continue this research with a qualitative approach, where several variables that have no significant effect can be studied and analyzed by several key stakeholders who have a direct role in economic growth, so that further research models can be better.